Pengembangan Website E-Commerce sebagai Media Iklan Menggunakan CMS Wordpress pada UMKM Septa Classic Motor Kota Batu - Nandra Agung Wicaksono; Fatkhur Rochman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The advancement of digital technology has encouraged MSMEs to utilize e-commerce websites as effective advertising medium. Septa Classic Motor MSME in Batu City has strong potential, yet its current website remains suboptimal in design and information structure. This research aims to develop a website using WordPress CMS 6.7.1 and measure its effectiveness as an advertising medium. This research employed action research, utilizing Figma to design the e-commerce website framework for Septa Classic Motor. The research applied purposive sampling, involving 2 computer experts, 2 marketing experts, the owner of Septa Classic Motor MSME, and 25 prospective or existing customers. The results were analyzed using descriptive statistical method. The results showed that the quality level of the developed e-commerce website was rated 'very good' category with a WebQual score of 0.8 and its effectiveness as an advertising medium was categorized as effective with an EPIC Model score of 3.80. These results indicate that the developed website is feasible for use and highly effective as an advertising medium for Septa Classic Motor. The e-commerce website is also expected to enhance SEO (search engine optimization) strategies effectively.